An empirical investigation on the drivers of income redistribution across OECD countries - Causa, Orsetta (OECD Economics Department Working Papers, 2018)
This paper provides an empirical investigation on the drivers of tax and transfer income redistribution to working-age households across the OECD over the last two decades, in a context where it has been declining in the vast majority of countries. The analytical approach is based on a reduced-form model of income redistribution which is estimated through cross-country-time series regressions. The baseline model builds on the political economy literature of income redistribution and includes a set of non-policy drivers such as labour market and socio-demographic conditions as well as measures of globalisation and technological change. The baseline model is augmented with major direct policy drivers of income redistribution covering tax revenue and social spending as well as a selection of tax and transfer policy parameters. Changes in the size of the tax and transfer systems likely to have contributed to the decline in income redistribution include the decline in social spending on cash support for working-age population and the diminishing role of personal income taxes in reducing inequality under the effect of increasing trade openness. Changes in specific tax and transfer policy instruments and parameters likely to have contributed to the decline in income redistribution include a flattening of the tax schedule in the upper-part of the wage distribution, a decline in the generosity and duration of unemployment-related transfers, including cuts to social assistance, and pension and early retirement reforms to encourage longer working life